2020
DOI: 10.3390/prosthesis2020006
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Treatment of Edentulous Maxillae with Overdenture Fully Supported by a Cad/Cam Titanium Bar with a Low-Profile Attachment Screwed on Four or Six Implants: A Case Series

Abstract: Rehabilitation of atrophic maxilla still remains a challenge. Fixed implant-supported restorations have become more predictable in the last years; nevertheless, technical and biological complications still occur. Removable overdenture fully supported by a CAD/CAM titanium bar seems to be a viable treatment option for the rehabilitation of completely edentulous patients with a high degree of bone resorption. In these clinical cases, the soft tissues of the lower third of the face need to be respected, and a fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The present study reports the three-year outcome of a restoration solution for full-arch edentulism comprised of a fixed hybrid polymer-acrylic prosthesis with CAD/CAM infrastructure, as an alternative to other recent CAD/CAM solutions [49].…”
Section: Discussionmentioning
confidence: 99%
“…The present study reports the three-year outcome of a restoration solution for full-arch edentulism comprised of a fixed hybrid polymer-acrylic prosthesis with CAD/CAM infrastructure, as an alternative to other recent CAD/CAM solutions [49].…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of long‐term randomized clinical trials involving a large sample size to determine a proper treatment protocol for the potentially edentulous maxilla 8 . However, a maxillary denture without palatal coverage, supported by 4‐6 implants, were shown to be successful 8,19 . A collective 10‐year survival rate of 99.3% was reported for 4‐6 splinted implant‐retained RCD compared to 85.7% for two independent implant‐retained RCD 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A bar‐splinted, implant‐retained RCD has long‐term reliability concerning the preservation of bone 25 . Some studies reported the bar's fabrication using CAD/CAM technology 19,22,26 . A CAD/CAM technology reduces the chance of casting errors, and using a titanium bar reduces the weight; however, the cost is usually on the higher side 26 .…”
Section: Discussionmentioning
confidence: 99%
“…connected by a metal or titanium bar, considering also the shape of the maxillary arch [7]. In this specific therapy, the prosthesis could have a limited palate, improving the patient's comfort and flavor perception [8].…”
Section: Methodsmentioning
confidence: 99%
“…In the mandible, two implants seem to be sufficient to obtain good stabilization of the removable prosthesis and the literature does not show statistically significant differences in terms of survival rate and comfort for the patient between insertion of two or four implants, solidified by a bar or with connections not constraining the implants (i.e., ball-attachment or other individual attachment type) [6]. On the other hand, for the upper maxilla the insertion of only two implants is not considered an ideal option if long cantilevers are expected; more predictable results could be achieved with the insertion of at least four implants connected by a metal or titanium bar, considering also the shape of the maxillary arch [7]. In this specific therapy, the prosthesis could have a limited palate, improving the patient's comfort and flavor perception [8].…”
Section: Introductionmentioning
confidence: 99%